2015
DOI: 10.1007/s00217-015-2612-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different ageing techniques on the polysaccharide and phenolic composition and sensorial characteristics of Chardonnay white wines fermented with different selected Saccharomyces Cerevisiae yeast strains

Abstract: Polysaccharides, mainly mannoproteins, play an important role on technological and sensory quality of wines. These compounds are released to the wine during alcoholic fermentation and, thereafter, during yeast autolysis in the ageing process. The effect of the ageing on lees and other alternative ageing techniques were studied in Chardonnay Chilean white wines previously fermented with different Saccharomyces cerevisiae yeast strains (Zymaflore VL2 and Lalvin CY3079). The Lalvin CY3079 released higher amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…During stress situations, including the presence of other microorganisms, significant modifications of protein synthesis are established, inducing an increase in protein production that may be subjected to hydrolysis releasing peptides ( Pereira et al, 2021 ). In addition, the S4 strain has been described as undergoing early autolysis, inducing the release of nitrogenous compounds including peptides ( del Barrio-Galán et al, 2016 ). Also, it is possible that this autolysis is stimulated by the presence of another strain.…”
Section: Resultsmentioning
confidence: 99%
“…During stress situations, including the presence of other microorganisms, significant modifications of protein synthesis are established, inducing an increase in protein production that may be subjected to hydrolysis releasing peptides ( Pereira et al, 2021 ). In addition, the S4 strain has been described as undergoing early autolysis, inducing the release of nitrogenous compounds including peptides ( del Barrio-Galán et al, 2016 ). Also, it is possible that this autolysis is stimulated by the presence of another strain.…”
Section: Resultsmentioning
confidence: 99%
“…The MQ3 strain induced a lower pH value and volatile acidity, which is beneficial toward enhancing the microbial stability and ensured wine quality (Lachowicz et al 2017, Duan et al 2018). Several studies have shown that yeasts have variable ability to adapt the wine biotope and to release β ‐ glycosidase leading to significant changes in the physicochemical indexes (Rodriguez‐Nogales et al 2012, Barrio‐Galán et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they could be useful in order to improve the roundness and softness in the mouth, especially in young wines that are more astringent (Del Barrio-Galán et al, 2012). It has also been reported that supplementation with commercial inactive yeasts in grape juice during winemaking and oak aging can significantly decrease the proanthocyanidin content of red wines coinciding with a decrease in high molecular weight mannoproteins (Del Barrio-Galán et al, 2016). This suggests that the co-aggregates mannoprotein-tannin precipitate during treatment (González-Royo et al, 2017).…”
Section: Maceration and Fermentationmentioning
confidence: 99%